Sodium alginate encapsulated iron oxide decorated with thymoquinone nanocomposite induces apoptosis in human breast cancer cells via PI3K-Akt-mTOR pathway - Alzahrani, Badr; Elderdery, Abozer Y.; Alsrhani, Abdullah; Alzerwi, Nasser A.N.; Althobiti, Maryam Musleh; Elkhalifa, Ahmed M.E.; Rayzah, Musaed; Idrees, Bandar; Kumar, Suresh S.; Mok, Pooi Ling (Elsevier, 2023)
The present study investigated the cytotoxicity and proapoptotic properties of iron oxide-sodium-alginate-thymoquinone nanocomposites against breast cancer MDA-MB-231 cells in vitro and in silico. This study used chemical synthesis to formulate the nanocomposite. Electron microscopies such as scanning (SEM) and transmission (TEM), Fourier transform infrared (FT-IR), Ultraviolet-Visible, Photoluminescence spectroscopy, selected area (electron) diffraction (SAED), energy dispersive X-ray analysis (EDX), and X-ray diffraction studies (XRD) were used to characterize the synthesized ISAT-NCs and the average size of them was found to be 55 nm. To evaluate the cytotoxic, antiproliferative, and apoptotic potentials of ISAT-NCs on MDA-MB-231 cells, MTT assays, FACS-based cell cycle studies, annexin-V-PI staining, ELISA, and qRT-PCR were used. PI3K-Akt-mTOR receptors and thymoquinone were predicted using in-silico docking studies. Cell proliferation is reduced in MDA-MB-231 cells due to ISAT-NC cytotoxicity. As a result of FACS analysis, ISAT-NCs had nuclear damage, ROS production, and elevated annexin-V levels, which resulted in cell cycle arrest in the S phase. The ISAT-NCs in MDA-MB-231 cells were found to downregulate PI3K-Akt-mTOR regulatory pathways in the presence of inhibitors of PI3K-Akt-mTOR, showing that these regulatory pathways are involved in apoptotic cell death. We also predicted the molecular interaction between thymoquinone and PI3K-Akt-mTOR receptor proteins using in-silico docking studies which also support PI3K-Akt-mTOR signaling inhibition by ISAT-NCs in MDA-MB-231 cells. As a result of this study, we can conclude that ISAT-NCs inhibit the PI3K-Akt-mTOR pathway in breast cancer cell lines, causing apoptotic cell death.